2020
DOI: 10.1002/ana.25862
|View full text |Cite
|
Sign up to set email alerts
|

Alertness Training Improves Spatial Bias and Functional Ability in Spatial Neglect

Abstract: We conducted a multisite, randomized, double-blinded, controlled trial to examine the effectiveness of a digital health intervention targeting the intrinsic regulation of goal-directed alertness in patients with chronic hemispatial neglect. Methods: Forty-nine participants with hemispatial neglect, who demonstrated significant spatially biased attention after acquired brain injury, were randomly assigned to the experimental attention remediation treatment or the active control group. The participants engaged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Indeed, it has been recognized early on that a punctual enhancement of alerting can trigger a transitory amelioration of hemispatial neglect symptoms ( Robertson et al , 1998 ). Consequently, several therapeutic approaches have been devised, aiming at ameliorating hemispatial neglect symptoms through an alerting enhancement ( Chandrakumar et al , 2019 ; Van Vleet et al , 2020 ), showing promising results on a group level. However, a great variability between individuals in treatment outcomes is a very common finding for neglect rehabilitation ( Bowen et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been recognized early on that a punctual enhancement of alerting can trigger a transitory amelioration of hemispatial neglect symptoms ( Robertson et al , 1998 ). Consequently, several therapeutic approaches have been devised, aiming at ameliorating hemispatial neglect symptoms through an alerting enhancement ( Chandrakumar et al , 2019 ; Van Vleet et al , 2020 ), showing promising results on a group level. However, a great variability between individuals in treatment outcomes is a very common finding for neglect rehabilitation ( Bowen et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This measure acknowledges that considering accuracy and response time separately may not capture the whole picture in patients’ cognitive decline. IES is widely used to measure cognition in healthy subjects as well as in patients with neurological injury [ 39 , 40 ] because it enhances the validity of cognitive measures reflecting “the average energy consumed by the system” [ 41 ]. When responding to a cognitive task, participants can be fast at the expense of accuracy or accurate at the expense of speed, yielding to a so-called “speed accuracy trade-off” [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In con trast to such patho log i cal crav ings, we look at mild crav ings as some thing that, via sa lience and meaningfulness of stim uli, helps pa tients sustain at ten tion through out re ha bil i ta tion and be come more vig i lant [45]. Sev eral stud ies have shown that en com passing is sues such as com puter games that trig ger re ward circuits in the mesolimbic do pa mine sys tem in re ha bil i ta tion lead to im prove ments in SN, both re lated to tonic and phasic alert ness [46,47]. It is, how ever, sur pris ing that var i ous com put er ized meth ods have not been cou pled with more per son al ized unique stim uli to help cap ture pa tients' at tention and im prove their re sponse time within the ne glected space.…”
Section: Ne Glect and Re Ha Bil I Ta Tionmentioning
confidence: 99%